PERAN PENDIDIKAN AGAMA AGAMA KRISTEN SEBAGAI UPAYA DALAM MENANGKAL RADIKALISME AGAMA DI INDONESIA - Fredik Melkias Boiliu (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2020)
This paper is an attempt to include the role of Christian religious education as a strategy in counteracting religious radicalism in Indonesia. The role of Christian religious education is very important in the lives of families, schools, churches and in the midst of plural society. The presence of Christian religious education in the midst of plural society becomes very important so that believers can live and apply their faith in daily life. The challenge of Christian religious education today is radicalism. Radicalism is an understanding that requires a change, turnover, and penetrating a community system to the root. Radicalism wants a total change in a condition or all aspects of community life. Radicals assume that the plans used are the most ideal plans. The meaning of radicalism in a religious perspective can be interpreted as a religious understanding that refers to a very basic religious foundation with a very high religious fanaticism, so it is not uncommon for adherents of these understandings / sects to use violence to actualize the religious understanding held and believed. In this case, there are several characteristics that can be identified from radical attitudes and understandings, namely, intolerance (not wanting to respect the opinions and beliefs of others), fanatics (always feeling right on their own; think others are wrong), exclusive (assuming their religion is the most correct) and revolutionary (tend to use violent means to achieve goals). Seeing the development of radicalism that is increasingly developing in Indonesia, especially radicalism in religion, we try to include Christian religious education as a strategy in counteracting religious radicalism through teaching Christian religious education in families, churches, schools and even in the midst of plural society